1999
DOI: 10.1017/s0266462399152127
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effect of Cesarean Section Rate on Health Outcome

Abstract: This paper tests the null hypothesis of a zero effect of cesarean section rate on health outcome against the alternative of a positive effect. Using data from 59 hospitals in Sweden from 1988-92, we specify two separate linear regression models for health outcome, one with perinatal mortality, and the other with rate of asphyxia, as dependent variable. We estimate the models by single-year cross-section regressions and as pooled data systems. The null hypothesis cannot be rejected, i.e., we do not find any sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
(17 reference statements)
1
14
0
1
Order By: Relevance
“…It is doubtful that surgical intervention during labor and delivery contribute to better outcomes; at best, cesarean section is a useful adjunct in keeping mortality low. The literature supports the contention that high rates of instrumental or surgical deliveries are not associated with improved perinatal outcomes (23,27‐31). Nonetheless, we should not completely dispel the alternative explanation that modern obstetric interventions, other than cesarean section or assistance with forceps and suction, contributed to the fall in the mortality indices.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It is doubtful that surgical intervention during labor and delivery contribute to better outcomes; at best, cesarean section is a useful adjunct in keeping mortality low. The literature supports the contention that high rates of instrumental or surgical deliveries are not associated with improved perinatal outcomes (23,27‐31). Nonetheless, we should not completely dispel the alternative explanation that modern obstetric interventions, other than cesarean section or assistance with forceps and suction, contributed to the fall in the mortality indices.…”
Section: Discussionmentioning
confidence: 60%
“…Given the lack of data on individual mother‐infant pairs, and the limited number of data points available (i.e., 8 years), on an aggregate level we were unable to control for these potential confounders through study design, stratification of results, or post‐hoc adjustment using multivariate techniques such as regression analysis. Furthermore, a descriptive, correlational study such as this one cannot establish cause and effect, although most components of our observations have been examined with other designs and in different settings (9,10,23,27‐32). Despite these potential shortcomings inherent in a population‐level study with a limited sample size, the associations we found, and also perhaps those we did not include, suggest the urgent need for further investigation into which factors related to the doctors' and women's decision‐making processes influence cesarean section rates.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal rate of CS for the average population in a high‐resource country is controversial. A World Health Organization consensus conference stated that the CS rate should not exceed 10–15% in any population, which has been confirmed by several authors . However, there have been concerns that if a CS rate of only 10–15% is aimed at, the wellbeing of the neonate might be endangered .…”
Section: Introductionmentioning
confidence: 97%
“…As well as the rate of CS, the incidence of maternal and neonatal complications varies markedly from hospital to hospital, even within the same country . There are some well‐known maternal and obstetric factors which increase the risk of maternal complications in CS .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the region, healthcare professionals consider higher rates to be unjustified in light of the frequency of obstetric complications [2–4]. Nevertheless, cesarean sections (C-sections) are among the most common surgeries performed, with increasing frequencies being observed in developed and developing countries [5–9].…”
Section: Introductionmentioning
confidence: 99%